De la cassette au fichier numérique : enjeux de l’archivage, du partage et de la restitution des archives orales enregistrées au Niger - Véronique Ginouvès; Ibrahim Moussa (Revue des Mondes Musulmans et de la Méditerranée)
This article, co-authored by a sociologist at the André Salifou University (Zinder, Niger) and an archivist at the Sound Archives Centre of the Maison méditerranéenne des sciences de l’homme (Aix-en-Provence, France), explores the many ways in which sound archives recorded in Niger by researchers from different disciplines in the humanities and social sciences can be revitalised. A brief historical overview of recording methods in the African field highlights the importance of documenting the context of their production and archiving in order to ensure their audibility and facilitate their use. While considering the restitution to the field of collections recorded on the Nigerian territory and preserved in France, the authors adopt a comprehensive and continuous approach to take into account a decisive paradigm shift: the understanding of analogue archives converted into digital format and their production in a colonial context with a view to postcolonial use. In this endeavour, Digital Humanities play a facilitating role by promoting the analysis, comparison and sharing of sound archives among all relevant stakeholders. The mapping of heritage and scientific archives created in this way would offer new perspectives on the culture and history of Niger, supporting the process of restoring oral archives for scientific, cultural and creative use.